EMBRACING LEARNERS WITH DISABILITY: WEB 2.0, ACCESS AND INSIGHT - Ellis, Katie (Swinburne University of Technology, 2011)
Like web 2.0, a participatory culture is central to university life. Several theorists have recognized the importance of digital technologies in including students with disability. Mainstream accessibility measures are beneficial to both students with disabilities and those without. Data for this paper is entirely crowd sourced from web 2.0 platforms and explores the ways students with disabilities are using mainstream accessible web 2.0 technologies - file sharing, Facebook, FourSquare and blogs - to foster inclusion. By utilizing the knowledge of the crowd this paper seeks to empower the disability narrative. People with disabilities are not just assisted by web 2.0, they are innovators of it.